MYC functions as a switch for natural killer cell-mediated immune surveillance of lymphoid malignancies - Srividya Swaminathan (Nature Portfolio, 2020)
Oncogene addiction is considered as a cancer cell-autonomous phenomenon, but can also influence the host immune system. Here the authors show that MYC-driven lymphomagenesis is associated with a block in the maturation and effector functions of natural killer cells as a mechanism of tumor escape from immunosurveillance.